Modelling freeway pedestrian crossing behaviour in Cape Town - Dada, Mercy (Centre for Transport Studies, 2019)
South Africa’s Freeway Management System (FMS) in Cape Town has recorded an alarming increase in pedestrian activity on its freeways in recent years, with a similar trend in (fatal) freeway pedestrian crashes. Both South African and international studies have demonstrated the relevant factors that account for the choices of pedestrians to cross roadways, while few studies have looked at freeway crossing. This study was undertaken to identify and estimate the factors that influence illegal freeway crossing using a discrete choice experiment in Cape Town. It is hypothesized that freeway pedestrian crossing is driven by personal factors and the perceived contribution thereof to the risks associated with the crossing using a footbridge or (illegally) at-grade. Using a stated choice survey including a perceived crossing risk assessment to estimate a series of choice models and based on a 300 participants survey, intercepted along three Cape Town freeways, ordered-responses logit models were developed to estimate risk perception thresholds for both general risk perception (prior to the choice experiment) as well as choice – task specific risk perception. Furthermore, basic and mixed logit models were estimated for freeway crossing choice. Correlations between risk perception and the crossing choices using a Cholesky transformation matrix were established. Finally, the implied relative sensitivities, or tradeoffs, between at-grade and footbridge crossing alternatives were estimated. The findings of this study confirm that, as expected, crossing choice is largely influenced by a combination of built environment, vehicular and pedestrian traffic, as well as socio-demographic characteristics. Among the 8 selected factors, traffic, walking distance and law enforcement presence were observed to be most vital in influencing the risk perception of pedestrians. Results show that younger pedestrians were more risk seeking than their older counterparts and that tenure - the length of time that a pedestrian has lived in Cape Town reduces the risk perception levels of traffic safety. Moreover, pedestrians were more likely to cross with the footbridge rather than directly under normal circumstances. As pedestrian safety is a part of policy interventions in transport, this thesis also suggests an approach to solve the problem of illegal freeway crossing. The results of this study can inform opportunities to counter the upward trend of fatalities and provide suggestions for policy-making, interventions and campaigns that would lead to improved freeway crossing safety.